E-Mail as a Source of Stress and Burnout Symptoms: The Mediating Role of Work-Family Conflict - Delgado, F.; Silva, S.A. (Work, Stress, and Health 2021, 2021)
Despite some findings that e-mail use can lead to symptoms of burnout and the experience of work-family conflict, no studies have addressed the relationship between e-mail as a source of stress and both burnout symptoms and work-family conflict. Additionally, no previous research has tested the mediation effect of work-family conflict in the relationship between e-mail as a source of stress and burnout symptoms. We conducted a cross-sectional study, in which 389 employees from a multinational company responded to an online survey. Our results provide evidence to consider that e-mail as a source of stress is likely to cause a conflict between an individual’s work and family domains, which by its turn, will lead to the experience of burnout symptoms.